Urban residential heating in hot summer and cold winter zones of China—Status, modeling, and scenarios to 2030. (May 2016) - Hu, Shan; Yan, Da; Cui, Ying; Guo, Siyue
Abstract: Space heating energy consumption in urban residential areas of the hot summer and cold winter zones (HSCW) in China has increased dramatically during the last decade. Large-scale surveys and in-depth measurements of residential heating consumption is important to monitor trends. More importantly, a macro energy model that reflects the current status and that can be used to analyze future scenarios is needed. In this paper, a bottom-up model was established, and the results show the total energy consumption in the HSCW and the influences of building envelops, heating equipment efficiency, and especially occupant behavior on energy use. Related technical and policy suggestions were analyzed in different scenarios. Presently, energy consumption for heating in urban residential areas of the HSCW is relatively low, but is increasing rapidly, so the establishment of superior national building energy efficient designs requires attention. The findings suggest that the district heating network would not be feasible for the HSCW and decentralized heating should be the major heating method employed. Besides building efficiency, appliance efficiency should also be improved. Lastly, residents' behaviors in regards to the opening of windows can significantly influence energy use and should be carefully considered by policy makers and engineers. Highlights: Energy consumption for HSCW zones in China low but increasing rapidly. Large variations of heating intensity due to heating system and occupant behaviors. Scenario analysis of heating energy consumption in 2030. Centralized district heating system is not feasible for the HSCW zones. Heating efficiency and energy-saving behaviors should be promoted.